Nurses’ perceived work environment in the public sector tertiary care hospitals of Khyber Pakhtunkhwa in Pakistan (Annals of Medical Research, 2021)
Aim: Aim of the study is to evaluate nurses’ perceptions regarding their work environment in the public sector tertiary care hospitals of Khyber Pakhtunkhwa in Pakistan.Materials and Methods: A cross-sectional study design was conducted from March-July 2019. Multi stage sampling method was selected. First we obtained four strata of the total 13 hospitals and then randomly selected four hospitals from the four strata. Three hundred and thirty-nine registered nurses were proportionately recruited from the each hospital through simple random sampling into the study from four major tertiary care teaching hospitals of Khyber Pakhtunkhwa in Pakistan. A self-reported scale Perceived work environment and nurses work index (PWES&NWI) was distributed among the study participants. Grand mean score < 2.5 of each component were taken for a favorable work environment and grand mean > 2.5 for taken for unfavorable work condition.Results: In a sample of 339(80%) of the nurses were female while the mean age of the participants was 30.8 years. Grand mean scores of the four components namely: nurse participation in hospital affairs, nurse foundation for quality of care, nurse manager ability and, availability of adequate resources were >2.5 except collegial nurse-physician relationship grand mean was 2.3. These results indicate that nurse’s work environment was unfavorable for practice. There was a statistically significant association between gender, current work units, and education with the five subscales of the nurse’s work environment (p
Keywords: Favorable; nurses; perception; tertiary care hospital; unfavorable; work environment